Carbon materials functionalized by nitrogenous ligands for dual application in energy storage and production: Fuel cells and supercapacitors. (10th May 2022) - Fruehwald, Holly M.; Melino, Peter D.; MacLean, Brian J.; Zenkina, Olena V.; Easton, E. Bradley
Abstract: Dual-purpose fuel cell/supercapacitor materials were made by covalent embedding of phenazin-iron adducts into various commercial carbon supports (Vulcan XC-72, Black Pearls 2000, Ketjen Black 600). The diazonium coupling reaction allows for controlled deposition of nitrogen functionalities to the carbon supports via the formation of the strong carbon-carbon bond between the nitrogenous ligand and carbon surface. The novel phenazin-functionalized carbon supports were prepared and fully characterized using thermogravimetric analysis, Raman spectroscopy, and BET pore size determination. Notably, the micro-and macrostructure and the porosity of the carbon support drastically affected the catalytic activity of the system in oxygen reduction reaction (ORR). The KB-phenazin-Fe-700 showed the highest activity for the ORR in both basic and acidic media. Interestingly, the heat treatment of the phenazin-based materials resulted in a significant increase in the ORR activity that is different from the trend we previously observed for terpyridine-based catalysts on Vulcan carbon that were demonstrating a significant decrease in the activity after heat treatment. Furthermore, the potential of the same materials to be used for energy storage was explored and their performance as supercapacitors was studied. The modification of the carbon surfaces by phenazin ligand shows significant improvement of the specific capacitance when examined in acidic media. Coordination of iron to the surface results in a further increase of the specific capacitance due to the additional Faradaic contributions. Drastic increases were seen in the capacitance when Fe was added to the BP-phenazin system. Interestingly, the heat treatment process was found to decrease the energy storage ability of the materials with a significant decrease of the specific capacitance. Thus, for phenazin-based materials, the heat treatment is a necessary step for the production of effective ORR catalysts but is undesirable for materials targeting mainly energy storage applications. Graphical abstract: Image, graphical abstract